PENGARUH MANAJEMEN PERSEDIAN DAN KEPEMIMPINAN TERHADAP KINERJA KELOMPOK TANI (Universitas Mitra Indonesia, 2020)
ABSTRACTThe purpose of this study is to analyze (1) the effect of inventory management, and (2) leadership on theperformance of Kelompok Tani Dwi Karya (Farmer Group) in Purwodadi Village, Trimurjo sub-district. The technique in selecting the sample used is Probability Sampling. This study uses a quantitative approach. The data collection tool in this study is a questionnaire. The data collected were analyzed using multiple linear regression analysis techniques with IBM SPSS 20 tools. The results showed that inventory management had a positive effect on the performance of farmer groups. Leadership has a negative effect on the performance of farmer groups. As well as inventory management and leadership simultaneously affect the performance of farmer groups.Keywords: Inventory Management, Leadership, Farmer Group Performance.